Silver threads: Unraveling the role of nucleolar organizer regions in breast tumors - Sushma N. Ramraje; Snehal P. Kosale; Diksha A. Dahake (Annals of Oncology Research and Therapy, 2025)
BACKGROUND: Nucleolar Organizer regions (NORs) are loops of DNA actively associated with nucleolus, which code for ribosomal RNA consisting of nonhistone proteins, which are argyrophilic. They are demonstrated as black, brown dots on staining with silver stains, so are called argyrophilic nucleolar organizer regions (AgNORs). MATERIALS AND METHODS: A total of 151 cases presenting with breast lump were included in the study. After histopathological diagnosis, the AgNOR staining technique according to guidelines by the International Committee on AgNOR quantitation was employed. AgNOR count was done on both benign and malignant tumors and correlated. RESULTS: The study included 151 female patients presenting with the complaint of a lump in the breast. The average age for benign tumors was 30.8 years and for malignant tumors was 43 years. The most common benign tumor was fibroadenoma and the most common malignant tumor was invasive ductal carcinoma. AgNORs were counted as well-defined black-silver binding dots within the light yellow staining nuclei. The grading of AgNOR size variation, dispersion of AgNOR dots and mean AgNOR score counted was higher in Malignant tumors when compared to benign tumors. CONCLUSION: The use of AgNOR in pathology across various branches continues to be a valuable adjunct to conventional diagnostic methods, offering additional insights into cellular behavior and disease progression, ultimately improving patient care and outcomes.